Caminhos da educação bilíngue: uma análise sobre a proposta de ensino para a educação infantil de uma escola de Goiânia - Silva, Valéria Rosa da (2012)
This study presents an analysis of the educational proposal offered by a school that calls itself bilingual and is part of the private schools of Goiânia, offering an instruction in Portuguese and English for children from two years old on. Given this context, this study aims: (1) to identify how the model of "bilingual education" presented by the school is structured; (2) to comprehend how languages are distributed through the curriculum and what are the policies for use of English and Portuguese in the school context; (3) to identify what are the uses and functions of English and Portuguese in pre-k classroom; (4) to identify which teaching activity is more common in this classroom and (5) to check for actions or projects that contribute for the enrichment of the bilingual proposal. Therefore, it has been adopted as a methodological paradigm the principles of education ethnography (ERICKSON, 1985; ANDRÉ, 1995). The results suggest that the school conception of bilingual education is that of language as a symbolic capital (BOURDIEU, 1998) and it offers a particular kind of English teaching which is not consistent with the bilingual education programs described in this research area (GENESEE, 1987; HORNBERGER, 1991; HAMERS; BLANC, 2000; BAKER, 2006). This study also showed that, in pre-k classroom, the English language communication is made possible by strategic resources such as contextualization strategies (GUMPERZ, 2002) and codeswitching (CANAGARAJAH, 2001; MEJÍA , 2002;MELLO, 2002), which act as scaffolding (VYGOTSKY, 2003) in the interaction between teacher and students. It is hoped that this study contributes to children bilingual education and bilingualism researches.